Realizing Minimum Service Standards for Food Based on Local Wisdom in Central Halmahera Regency - Abdurachman F, Maman (Agrikan Jurnal Agribisnis Perikanan, 2020)
This study is a descriptive subjective which tries to integrate between intuitive experience and an understanding of the opportunities that exist The essence of local wisdom to food based on several previous studies and studies shows that there are other values that accompany it, namely the realization of food security in the area concerned. which states that “vulnerability to food insecurity with local wisdom is smaller than on vulnerability to food insecurity without local wisdom. One of the efforts to increase the acceleration of the movement to diversify food consumption in order to achieve food security is to restore the diversification pattern of food consumption that has taken root in society as local wisdom, by exploring and developing local wisdom, it can not only be relieving, but can also be avoided (preventing) due to the large amount of resources for the next generation. The results of the study here ultimately point to the efforts that need to be done, namely: (1). Preserving Local Wisdom and Culture on Food, (2). Collaborating skills with local wisdom on food, (3). Focus on cultivating selected superior commodities, (4). Capacity and capability enhancement, and (5). Synergy, integrity, communication and collaboration between related agencies. From the results of this study, it is hoped that the Regional Government as a stakeholder should be consistent and committed to implementing these efforts